Measurement data processing with the use of art networks = Przetwarzania danych pomiarowych z wykorzystaniem sieci z rezonansem adaptacyjnym ART - Mrówczyńska, Maria; Sztubecki, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
ART (Adaptive Resonance Theory) networks were invented in the 1990s as a new approach to the problem of image classification and recognition. ART networks belong to the group of resonance networks, which are trained without supervision.
Keywords: ART neural network; prediction model; vertical displacements; sieci neuronowe ART; model predykcyjny; przemieszczenia pionowe